Permanências e inovações: o projeto Mangabeira. - Leal, Anny Karinny Lima (2012)
This paper addresses the second phase of operation the National Housing Bank (BNH) (1977 - 1986) characterized by a phase of experimentation and criticism to the model supported housing production adopted in sets produced by the state. In this context, emerges a broad set experiences of municipal social housing, with great heterogeneity that appear alongside the traditional interventions, already applied by BNH. These experiences projetuais when compared to the model used by BNH in its early stages, adopt innovative assumptions as sustainable development, diversity of projects, participation processes and stimulating self managed in partnership with organized society. In this sense, this research aims to analyze the main project Set Mangabeira in light of transformations between the first and second phase of BNH.